Institutional Overlaps and Agency Autonomy: Examining Ministerial Influence on National Agencies’ EU Affairs - Kühn, Nadja S. (Scandinavian Journal of Public Administration, 2021)
Administrative integration across levels of government has raised questions about how it might affect political control over national agencies. This study asks what the key mechanisms are that might facilitate or impede ministerial influence over subordinate agencies’ implementation of EU rules and regulation. It argues that institutional overlaps, understood as coinciding organisational properties in agencies and ministries, leads to increased ministerial control. It tests the effect of three types of overlaps: administrative capacity, demography and site. With the benefit of a large-N dataset on Norwegian agency officials (N=1031) supplemented with qualitative interview data, the study examines how these organisational overlaps may account for ministerial influence over national agencies. The analysis reaffirms the explanatory value of organisational overlaps, but does not show significant effects of demography and site. Additionally, it suggests that involving agency officials in ministerial working groups might be an effective means to exert influence.